Correction: Thermally stable mesoporous tetragonal zirconia through surfactant-controlled synthesis and Si-stabilization. Issue 40 (15th September 2022) - Abel, Ken L.; Weber, Sebastian; Poppitz, David; Titus, Juliane; Sheppard, Thomas L.; Gläser, Roger
Abstract : Correction for 'Thermally stable mesoporous tetragonal zirconia through surfactant-controlled synthesis and Si-stabilization' by Ken L. Abel et al., RSC Adv., 2022, 12, 16875–16885, ; https://doi.org/10.1039/d2ra01459a .